Global trends in local contexts: The Finnish Embassy in Paris, 1956–1990 - Louis Clerc (De Gruyter, 2022)
A group of recent publications have reflected on the way the diplomatic machineries of small states have adapted to recent changes, upgraded engagement with global questions, reached out to experts and private actors, and increased organizational flexibility. This article aims to participate in this discussion. We will draw on Cristina Archetti’s insights in her study of the localized practices of foreign correspondents in order to inform a presentation of changes in the Finnish diplomatic representation in Paris. The case study suggests that the drivers of local evolutions are to be looked at not only in global trends but also in the interplay between the characteristics of the Finnish diplomatic network, the specificities of the country of residence, and wider political, cultural and commercial structures. The article makes the case for a localized, contextualized, fine-grained approach to the influence of global trends.